Development of Adventures in the World of Light (AiWoL) Comic: Understanding of the Light Concept - Aminudin, Adam Hadiana; Syamsiah, Endah Nur; Nabilah, Fatih Najah; Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad (Universitas Lambung Mangkurat, 2024)
This research aims to develop the Adventures in the World of Light (AiWoL) comic to understand the concept of the duality of light (as particles and waves). AiWoL tells the journey of the concept of the duality of light and is part of an Augmented Reality (AR) development project called Physics Virtual Technology Teaching Tools (PV3T). This development uses the Identify, Design, Development, Evaluation (IDDE) design. Validity sheets are given to physics, media, and conceptual psychology experts to see the feasibility of the AiWoL comic. Respondents at the evaluation stage were 39 students who had studied light waves (in the aspects of image clarity, language usage, and conceptual understanding). Meanwhile, Rasch analysis was used to identify the feasibility of the AiWoL comic based on the respondents' answers. The results showed that the instrument quality value in terms of the suitability of the physics concept (86), media feasibility (92), and psychology of conception (98) (all in the very good category). Meanwhile, the results of the Rasch analysis showed that the AiWoL comic feasibility instrument was reliable (0.94 (excellent)) and valid (56.1% (appropriate)). In addition, the AiWoL comic has aspects of Image clarity (83%), Language usage (85%), and Conceptual understanding (85%) (all in the very good category). These results also confirm no bias towards the semester and gender. Furthermore, the AiWoL comic will be used as part of the design for developing Physics Virtual Technology Teaching Tools (PV3T), which is an application based on Augmented Reality (AR).